Increased distribution of carbon metabolic flux during de novo cytidine biosynthesis via attenuation of the acetic acid metabolism pathway in Escherichia coli - Tong Ye; Wei Ding; Zhengxu An; Haojie Zhang; Xiaobo Wei; Junnan Xu; Huiyan Liu; Haitian Fang (Microbial Cell Factories)
Abstract Acetic acid, a by-product of cytidine synthesis, competes for carbon flux from central metabolism, which may be directed either to the tricarboxylic acid (TCA) cycle for cytidine synthesis or to overflow metabolites, such as acetic acid. In Escherichia coli, the acetic acid synthesis pathway, regulated by the poxB and pta genes, facilitates carbon consumption during cytidine production. To mitigate carbon source loss, the CRISPR-Cas9 gene-editing technique was employed to knock out the poxB and pta genes in E. coli, generating the engineered strains K12ΔpoxB and K12ΔpoxBΔpta. After 39 h of fermentation in 500 mL shake flasks, the cytidine yields of strains K12ΔpoxB and K12ΔpoxBΔpta were 1.91 ± 0.04 g/L and 18.28 ± 0.22 g/L, respectively. Disruption of the poxB and pta genes resulted in reduced acetic acid production and glucose consumption. Transcriptomic and metabolomic analyses revealed that impairing the acetic acid metabolic pathway in E. coli effectively redirected carbon flux toward cytidine biosynthesis, yielding a 5.26-fold reduction in acetate metabolism and an 11.56-fold increase in cytidine production. These findings provide novel insights into the influence of the acetate metabolic pathway on cytidine biosynthesis in E. coli. Graphical Abstract